2006
DOI: 10.1038/sj.sc.3101979
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury influences psychogenic as well as physical components of female sexual ability

Abstract: Study design: Secure, web-based survey. Objectives: Elicit specific information about sexual function from women with spinal cord injuries (SCI). Setting: World-wide web. Methods: Individuals 18 years or older living with SCI obtained a pass code to enter a secure website and then answered survey questions. Results: Bladder and/or bowel incontinence during sexual activity and/or sexual intercourse were significant concerns and prevented some women from seeking sexual activity. Autonomic dysreflexia (AD) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
3
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 26 publications
2
52
3
10
Order By: Relevance
“…7 The present study found that pain during intercourse did not significantly affect women's sexual functioning, which is similar to that found in previous studies. 4,19 Age was another predictor of the FSD in the present study. Others have found that women over age 30 years are associated with a decline in sexual interest.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…7 The present study found that pain during intercourse did not significantly affect women's sexual functioning, which is similar to that found in previous studies. 4,19 Age was another predictor of the FSD in the present study. Others have found that women over age 30 years are associated with a decline in sexual interest.…”
Section: Discussionmentioning
confidence: 78%
“…Women are more prone to depression and psychological disorders after injury compared with men. 4 Moreover, studies have found that women with SCI frequently report loss of vaginal lubrication and problems reaching orgasm. [4][5][6][7][8] Female sexual dysfunction (FSD) can often interfere with quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 According to the literature, women with SCIs have reduced ability to achieve orgasm; 50% are able to achieve it with level T12-L1 injuries, and o17% are able to achieve it with level S2-S5 injuries. 12 In our sample, 37% of the women were able to achieve orgasm.…”
Section: Sexual Satisfaction In Spinal Cord Injuries S Otero-villavermentioning
confidence: 99%